Clinical and Histopathological study of black and red grape seed extracts (Vitis Vinifera) effects on the Albino Mice - Snur M. A. Hassan1 , Shno N. Hassan2 , 3 Nian N.N.Maarof (Institute of Medico-legal Publications Pvt Ltd, 2021)
Grape seed extract (GSE) is a complex mixture of several compounds, mostly represented by polyphenolsand phenolic acids. The goal of the pilot study was to illustrate the safe dose of GSE in mice model andto assess toxicity that may be initiated by the different concentrations of this plant. Forty-two mice weredivided equally into 7 groups; groups 1 attended as control, were only received water, whereas animals ofgroups 2, 3, 4 were treated orally with 200, 400, and 800 mg/kg b.w. of black grape seed extract respectively,and the remaining groups including 5, 6, and 7 were treated orally with 200, 400, and 800 mg/kg b.w. ofred grape seed extract respectively. The animals were observed daily for any sign revealing for activityalterations and toxicity along with their body weight measurement during the experiment for 21 days withhistopathological examination. The results gained from this pilot study were recording that the 200 and 400mg/kg b.w. doses of GSE were safe compared to the 800 mg/kg b.w.in both black and red grape seed extractsbecause the higher dose led to a reduction in body weight gain and produce changes in the mentioned organs.